A quasi-spherical sodium zirconium phosphate powder, preparation method and application thereof
By controlling the molar ratio, particle distribution and the use of structural stabilizers of zirconium elements and phosphate, spherical sodium zirconium phosphate powder was prepared, which solved the problems of insufficient cation exchange capacity and structural instability of existing zirconium phosphate materials, and achieved efficient and recyclable hemodialysis materials.
Patent Information
- Application Number
- CN202410898645.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-05
AI Technical Summary
Existing zirconium phosphate materials have problems of insufficient cation exchange capacity, instability of structural and high cost in hemodialysis applications, especially in the maintenance of cation exchange capacity and the regeneration capacity of the material.
By controlling the molar ratio of zirconium element and phosphate, particle distribution, amount of active sodium ion introduction and the use of structural stabilizers, spherical zirconium phosphate sodium powder is prepared to improve its cation exchange capacity and structural stability.
It has achieved high cation exchange capacity of sodium zirconium phosphate powder, can be reused for more than 15 times, and maintained more than 90% of the exchange capacity, reducing the cost of hemodialysis, and improving the structural stability and regeneration ability of the material.
Smart Images

Figure CN118877852B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dialysis materials, and in particular relates to a quasi-spherical sodium zirconium phosphate powder, a preparation method and application thereof. Background Art
[0002] Zirconium phosphate is increasingly used in the fields of medicine, fine ceramics, catalyst carriers, optics, etc. due to its excellent physical and chemical properties. + Mg 2+ , Ca 2+ , K + Zirconium phosphate has a strong ion exchange capacity and regeneration capacity, and is considered to be an ideal hemodialysis material. It has great application potential in facilitating patient treatment and reducing the cost of hemodialysis. As a material for hemodialysis, the physical, chemical and biological indicators of zirconium phosphate have strict application restrictions, among which the physical indicators include the particle size distribution, density, Hausner ratio, water content, etc. of the powder, the chemical indicators include ion exchange capacity, element precipitation, sodium content, material pH, regeneration capacity, etc., and the biological indicators include endotoxin, total number of microorganisms, cytotoxicity, etc. Among all the indicators, the cation exchange capacity, especially the ammonium ion exchange capacity, is the most core indicator. The strength of the ion exchange capacity directly determines whether the material can be applied to the field of hemodialysis. It is well known that zirconium phosphate is a material with ion exchange capacity, but there is little research on the factors affecting the cation exchange capacity of zirconium phosphate and its derivatives. Since zirconium ions and phosphate ions can be combined in almost any molar ratio, not all zirconium phosphate materials have sufficient ion exchange capacity.
[0003] The group with ion exchange capacity in zirconium phosphate is the active hydrogen ion on the hydrated zirconium phosphate molecule, which can be used to adsorb cations such as ammonium ions, potassium ions, calcium ions, and magnesium ions produced by human metabolism to achieve the effect of hemodialysis. Active hydrogen ions have a certain ion exchange capacity, but its ion exchange capacity is insufficient. After introducing active sodium ions on the basis of active hydrogen ions, sodium zirconium phosphate is formed, and its cation exchange capacity is greatly enhanced compared with zirconium phosphate. However, sodium ions are not introduced infinitely, and excessive sodium ion content does not increase the cation exchange capacity infinitely. Within a certain range of introduced amounts, the cation exchange capacity of the formed sodium zirconium phosphate is stable and excellent.
[0004] Active hydrogen ions are the basis for the incorporation of sodium ions. The main factors affecting the active hydrogen ion content are the molar ratio of zirconium element and phosphate and the acidity of the slurry when forming zirconium phosphate. In addition, the cation exchange capacity of zirconium phosphate is also related to its particle size. Generally, the smaller the particle size, the larger the specific surface area, and the higher the cation exchange capacity it possesses. However, when the particle size is less than 10μm, or the particle size distribution is uneven, it will affect the flow of the dialysate in the zirconium phosphate powder, and its cation exchange capacity will be reduced. In addition, the active hydrogen ions on the zirconium phosphate molecules will gradually be lost as the water is lost during the drying process. Therefore, too high a drying temperature and too low a water content are not good for the cation exchange capacity of zirconium phosphate.
[0005] In order to reduce the dialysis cost of hemodialysis patients, sodium zirconium phosphate powder should also have excellent recycling and regeneration ability. The cation (NH4 + ) The exchange capacity is not less than 90% of the original powder, and the regeneration times are not less than 15 times. The regeneration ability of sodium zirconium phosphate depends on its original cation exchange capacity and the stability of its molecular structure. Therefore, good sodium zirconium phosphate powder is easy to regenerate. Use a sodium salt solution with an appropriate pH to slowly flow through the ineffective sodium zirconium phosphate powder, so that hydrogen ions and sodium ions replace the NH 4+ Mg 2+ , Ca 2+ , K + The cations are then returned to their original pH. Therefore, it is very important to maintain the structural stability of the sodium zirconium phosphate powder.
[0006] The structural destruction of sodium zirconium phosphate mainly occurs in two steps. First, in the process of preparing sodium zirconium phosphate, although zirconium phosphate is a stable substance that is insoluble in water, when sodium is added, the zirconium phosphate molecules will be forced to open the original structure, and the sodium ions will replace the active hydrogen ions in the zirconium phosphate to form a new sodium zirconium hydrogen phosphate structure. The stability of this structure is the basis for the reuse of sodium zirconium phosphate. Zirconium phosphate is fragile and easy to inactivate during the sodium addition reaction, which is mainly manifested in the particles becoming smaller and releasing a large amount of phosphate. In addition, due to the action of hydroxide, the active hydrogen ions in the zirconium phosphate may be consumed by hydroxide, greatly reducing the ion exchange capacity of zirconium phosphate. Second, during the ion exchange process, the complex ion composition in the dialysate may also cause the original molecular structure of sodium zirconium phosphate to change, such as the large amount of phosphate precipitation causing the powder molar ratio to change, and the active hydrogen ions or active sodium ions cannot be restored after being occupied.
[0007] In addition, phosphate and zirconium ions have a strong binding ability in the solution. Even under strong acidic conditions, phosphate and zirconium ions can instantly form insoluble zirconium phosphate precipitation. Therefore, it is difficult to form regular zirconium phosphate (or sodium zirconium phosphate) particles and control their particle size distribution. Therefore, in most cases, the molecular structure of the zirconium phosphate compound formed instantly is chaotic. In order to solve this problem, many existing technologies have studied the morphology regularization and performance of zirconium phosphate. For example, in Chinese Patent 201110272640.4, phosphoric acid and zirconium oxychloride are used as raw materials, and then stirred, washed, filtered and dried after adding diacid and ethylenediamine to obtain rod-shaped zirconium phosphate. For example, in Chinese Patent 201110352622.7, diammonium hydrogen phosphate, zirconium oxychloride and oxalic acid are used as raw materials and reacted at 140-160°C for 7-10h to obtain cubic zirconium phosphate. Among many studies, the research on layered α-zirconium phosphate is the most. Existing studies have shown that layered α-zirconium phosphate has good cation exchange capacity and has good application prospects in hemodialysis. The main process for preparing layered α-zirconium phosphate is mineralization hydrothermal reaction under high acidity conditions, such as the method described in Chinese Patent 201110134080.6, which includes solution preparation, high-pressure reaction, solid-liquid separation, water washing, drying and other processes; another example is the method described in Chinese Patent 201110134080.6, which uses zirconium oxychloride and sodium polyphosphate as raw materials to react in an autoclave to obtain sodium zirconium phosphate. In addition, another process for preparing layered α-zirconium phosphate is a high-temperature cyclic reaction under high acidity conditions.
[0008] However, there are obvious disadvantages in the application of layered α-zirconium phosphate in the field of hemodialysis. For example, fluoride is often required as a mineralizer or organic compounds are required as a structure modifier in its preparation process. The use of these materials seriously affects the purity of zirconium phosphate for hemodialysis. Hydrothermal reaction also requires high temperature and pressure conditions, and the requirements for production equipment are very high. In addition, the particle size of α-zirconium phosphate is only about 1μm, which is extremely unfavorable for the application of zirconium phosphate in hemodialysis. Too small molecular gaps will make it difficult to remove free phosphoric acid and other impurity ions in the molecular gaps. The free phosphorus precipitation in α-zirconium phosphate is usually as high as 10000ppm or more. Secondly, too small molecular gaps will cause blockage when the dialysate flows through the zirconium phosphate molecules. The pipeline pressure after blockage increases, and the adsorption tank will collapse and "breakdown", that is, the dialysate does not pass through the dialysis material and flows directly through the existing passage. Therefore, when using α-zirconium phosphate as a dialysis material, it is often necessary to granulate the material so that it can be polymerized to form particles of uniform size. For example, the method described in Chinese patent 200610164928.9 is to first prepare zirconium phosphate powder, then perform delamination to prepare zirconium phosphate colloid, and finally obtain 10-100 μm particles through a spray dryer; in the granulation process, adhesives and high temperatures are indispensable, wherein the role of the adhesive is to make α zirconium phosphate particles of about 1 μm agglomerate together, and the role of high temperature is to make the agglomerated particles form instantly. Commonly used adhesives are non-toxic polyethylene glycol (PEG) and some resin materials. Although the use of a small amount of adhesive is harmless, the adhesive will block the active groups (H + and Na + ), resulting in a decrease in cation exchange capacity. At the same time, the active groups on the molecular surface of zirconium phosphate are heat-sensitive, and high temperature will also lead to a decrease in the cation exchange capacity of zirconium phosphate. Another idea to solve this problem is to mix α-zirconium phosphate with other inert skeleton materials (such as silicon oxide, zirconium oxide, etc.) to fully disperse the α-zirconium phosphate in the adsorption tank, but the addition of inert skeleton materials will inevitably lead to a decrease in the ion exchange capacity of zirconium phosphate per unit volume. Therefore, the technical requirements for using α-zirconium phosphate as a hemodialysis material are very strict.
[0009] Therefore, it is of great significance to develop a sodium zirconium phosphate powder that has a stable molecular structure, is suitable for hemodialysis, has a high cation exchange capacity and can be recycled. Summary of the invention
[0010] The present invention provides a method for preparing spherical sodium zirconium phosphate powder, comprising the following steps:
[0011] (1) Preparation of zirconium-containing slurry
[0012] dissolving a zirconium raw material in water to prepare a zirconium-containing slurry;
[0013] (2) Preparation of initial H + Zirconium phosphate
[0014] The zirconium-containing slurry and phosphate raw materials are added to the reactor and reacted at 25-110°C and a stirring speed of >2.5 m / s to obtain the initial H + Type zirconium phosphate;
[0015] (3) Preparation of secondary H + Zirconium phosphate
[0016] At 25-110°C and stirring speed > 2.5 m / s, add the zirconium slurry to the primary H + The phosphate raw material is then added to the zirconium phosphate slurry to react and obtain the secondary H + Type zirconium phosphate;
[0017] (4) Slurry dehydration and reconditioning
[0018] The secondary H + The zirconium phosphate slurry is dehydrated and washed to remove free phosphorus and impurity elements, and then the dehydrated H + The zirconium phosphate was placed in water and re-prepared into H + Type zirconium phosphate slurry;
[0019] (5) Preparation of sodium zirconium phosphate slurry
[0020] In H + Sodium salt and structural stabilizer are added to the zirconium phosphate slurry, and reacted at 25-110°C and stirring speed>2.5m / s to perform sodium addition reaction and structural stabilization reaction to obtain Na + Type zirconium phosphate, i.e. sodium zirconium phosphate slurry;
[0021] (6) Obtaining sodium zirconium phosphate powder
[0022] The pH of the sodium zirconium phosphate slurry is adjusted to 2-10; the sodium zirconium phosphate slurry is dehydrated and washed to remove residual free phosphorus and impurity elements; the sodium zirconium phosphate solid is then dried at 30-270° C. to a moisture content of 8-20%, and the sodium zirconium phosphate solid is then sieved to remove lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder.
[0023] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (1), the zirconium raw material includes but is not limited to one or more of zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium carbonate, and zirconium acetylacetonate.
[0024] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in the step (1), the concentration of zirconium element in the zirconium-containing slurry is selected from 3 to 20%.
[0025] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (2), the phosphate raw material includes but is not limited to one or more of phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, and sodium dihydrogen phosphate.
[0026] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in the step (2), the amount of zirconium-containing slurry is selected from 10 to 70% of the total amount of zirconium-containing slurry, and the amount of phosphate raw material is selected from 10 to 70% of the total amount of phosphate raw materials, wherein, in this step, the amount of zirconium-containing slurry and the amount of phosphate raw material are the same in proportion to their respective total amounts.
[0027] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in the step (3), the amount of zirconium-containing slurry is selected from 30 to 90% of the total amount of zirconium-containing slurry, and the amount of phosphate raw material is selected from 30 to 90% of the total amount of phosphate raw materials, wherein, in this step, the amount of zirconium-containing slurry and the amount of phosphate raw material are the same in proportion to their respective total amounts.
[0028] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in the step (4), the re-prepared H + The concentration of zirconium element in the zirconium phosphate slurry is selected from 3 to 20%.
[0029] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (5), the sodium salt includes but is not limited to one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate.
[0030] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (5), the structural stabilizer includes but is not limited to one or more of sodium chloride, sodium sulfate, sodium nitrate, sodium metaphosphate, and sodium phosphate.
[0031] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (5), the structural stabilizer is in the form of H + The concentration of zirconium phosphate slurry is 0.1-10%, the structural stabilizer and H + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.03 to 1:1.
[0032] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (5), sodium salt and H + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.1 to 2:1.
[0033] In the above-mentioned method for preparing quasi-spherical sodium zirconium phosphate powder, in step (6), one or more of hydrochloric acid, phosphoric acid and sodium hydroxide are used to adjust the pH.
[0034] In the preparation method of the quasi-spherical sodium zirconium phosphate powder, the molar ratio of the zirconium element in the total amount of the zirconium-containing slurry used to the phosphate in the total amount of the phosphate raw material used is selected from 1:1.5 to 5.
[0035] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, in step (2), step (3) and step (5), the reaction time is at least 1 hour.
[0036] In the preparation method of the quasi-spherical sodium zirconium phosphate powder, the water is pure water, and its endotoxin value is less than 0.25EU / mL and its conductivity is less than 5us / cm.
[0037] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, the washing is to use pure water 10 to 80 times the weight of the sodium zirconium phosphate solid to wash the dehydrated sodium zirconium phosphate solid to remove residual free phosphorus and impurity elements.
[0038] In the above-mentioned method for preparing spherical sodium zirconium phosphate powder, the first H + When the type zirconium phosphate is prepared, the reaction of the zirconium element and the phosphorus element is carried out in the order of adding the zirconium element and the phosphorus element at the same proportion at the same time or first adding the zirconium and then adding the phosphorus at the same proportion.
[0039] The invention provides spherical sodium zirconium phosphate powder prepared by the method.
[0040] The present invention provides application of the quasi-spherical sodium zirconium phosphate powder in preparing hemodialysis materials.
[0041] The beneficial effects of the present invention are:
[0042] The present invention prepares sodium zirconium phosphate powder with high ammonium ion exchange capacity by controlling the molar ratio, particle distribution, active sodium ion introduction amount, maintenance of sodium zirconium phosphate molecular structure, suitable reaction temperature and drying conditions. The sodium zirconium phosphate powder has a regular morphology and is spherical. The present invention achieves technical breakthroughs such as orderly growth of sodium zirconium phosphate particles, molecular structure rearrangement, and molecular structure stability, forming a new sodium zirconium phosphate powder, which avoids the influence of small particle size or disordered particles on the performance of zirconium phosphate.
[0043] The present invention avoids structural destruction of zirconium phosphate by adding a structural stabilizer during sodium addition reaction, and stabilizes the structure of sodium zirconium phosphate powder by appropriate drying temperature and LOD control, so that when the sodium zirconium phosphate reacts with a dialysate, large-scale phosphate precipitation and molecular structure destruction will not occur due to ion exchange reaction, thereby ensuring that the regeneration capacity of the sodium zirconium phosphate and the cation exchange capacity after regeneration will not be greatly reduced.
[0044] The cation (NH 4+) exchange capacity can reach 30mmol / g, and its cation exchange capacity is increased by more than 30% compared with layered α zirconium phosphate. The sodium zirconium phosphate powder can be reused for more than 15 times, and after being reused for 15 times, its cation exchange capacity is not less than 90% of the original powder, and the powder has a simple regeneration method. After the sodium zirconium phosphate powder is saturated with cation adsorption, the regeneration capacity can be restored after washing with sodium salt and pH buffer, which greatly reduces the cost of hemodialysis. The sodium zirconium phosphate powder has an extremely narrow particle size distribution. Under this particle size distribution condition, it is easier to clean the impurity elements in the sodium zirconium phosphate. In addition, the sodium zirconium phosphate powder has a small Hausner ratio, which can effectively reduce the gaps caused by gravity and vibration after the adsorption tank is filled, and is conducive to the uniform flow of the dialysate through the adsorption tank to fully carry out the dialysis reaction. The sodium zirconium phosphate powder has better structural stability and higher structural strength, less element precipitation under the condition of dialysate immersion, and the zirconium element precipitation value in 37°C pure water is less than 10μg / g. The sodium zirconium phosphate powder has a low free phosphorus content. The free phosphorus value of the powder can be lower than 1500 mg / kg, which effectively reduces the amount of free phosphorus to be processed after the hemodialysis reaction and reduces the amount of zirconium hydroxide or sodium zirconium carbonate used.
[0045] The present invention avoids harsh process conditions, such as high-pressure and high-temperature reaction, strong acid thermal cycle reaction, etc., in the process of preparing sodium zirconium phosphate powder. At the same time, no additives harmful to human body, such as fluoride and other substances, are used in the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is a SEM image of zirconium phosphate without molecular structure rearrangement;
[0047] Figure 2 is the SEM image of layered α-zirconium phosphate prepared by hydrothermal method;
[0048] Figure 3 This is a SEM image of layered α-zirconium phosphate prepared by high temperature thermal cycling;
[0049] Figure 4 This is a SEM image of the sodium zirconium phosphate powder prepared in Example 1;
[0050] Figure 5 This is the particle size distribution diagram of the sodium zirconium phosphate powder prepared in Example 1. DETAILED DESCRIPTION
[0051] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0052] Example 1
[0053] The steps for preparing sodium zirconium phosphate powder are as follows:
[0054] 500 kg of zirconium oxychloride raw material was dissolved in 500 kg of pure water (endotoxin value < 0.25 EU / mL, conductivity < 5 μs / cm) to prepare zirconium oxychloride slurry [zirconium element (ZrO2 wt%) concentration of 18%].
[0055] 100 kg of zirconium oxychloride slurry (10% of the total amount) and 25.3 kg of phosphoric acid [concentration of 85% (10% of the total amount)] were slowly added to the reactor at the same time. The reaction temperature was maintained at 25 ° C. During the reaction, the stirring speed was maintained at 2.6 m / s to gradually form zirconium phosphate slurry. The slurry was maintained for 6 hours to obtain the initial H + Type zirconium phosphate.
[0056] 900 kg of zirconium oxychloride slurry (90% of the total amount) was slowly added to the above zirconium phosphate slurry. The reaction temperature was maintained at 25° C. and the stirring linear velocity was maintained at 2.6 m / s during the reaction.
[0057] 227.7 kg of phosphoric acid (90% of the total amount) was slowly added to the above zirconium phosphate slurry. The reaction temperature was maintained at 25 ° C. The stirring speed was maintained at 2.6 m / s during the reaction. During this process, the molar ratio of zirconium and phosphorus in the slurry reached 1:1.5, and the zirconium concentration (in terms of ZrO2 wt%) reached 20%. The reaction was continued for 2 hours to achieve molecular rearrangement and obtain secondary H + Type zirconium phosphate.
[0058] The obtained H + The zirconium phosphate slurry is dehydrated and washed with pure water, with the amount of washing water being 10 times the weight of the zirconium phosphate solid to remove most of the free phosphorus and impurity elements.
[0059] The dehydrated H + The zirconium phosphate type was placed in pure water again to re-prepare into zirconium phosphate slurry with a zirconium element concentration (measured in ZrO2wt%) of 20%.
[0060] 7.7 kg of sodium carbonate and 3.4 kg of sodium bicarbonate were added as sodium salt donors for the sodium addition reaction (sodium salt and H +The molar ratio of zirconium ions in the zirconium phosphate slurry is 0.1:1), and 82.9 kg of sodium chloride and 7.1 kg of sodium phosphate are added as structural stabilizers. The temperature is maintained at 110° C. and the stirring line speed is maintained at 2.6 m / s. Sodium addition reaction and structural stabilization reaction are carried out, wherein the concentration of the structural stabilizer in the slurry is 10%, and the molar ratio of the structural stabilizer to the zirconium ions in the slurry is 1:1. The reaction is carried out for 6 hours to obtain Na + Type zirconium phosphate, that is, sodium zirconium phosphate slurry.
[0061] The pH of the sodium zirconium phosphate slurry was adjusted to 2 with hydrochloric acid.
[0062] The obtained sodium zirconium phosphate slurry is dehydrated and washed with pure water, with the washing water amount being 10 times the weight of the sodium zirconium phosphate solid weight, to remove residual free phosphorus and impurity elements.
[0063] The sodium zirconium phosphate solid is dried at 270° C. to a LOD value of 8%, so that the material has fluidity and the structural stability of the sodium zirconium phosphate is enhanced.
[0064] The dried sodium zirconium phosphate solid is screened to remove the lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder.
[0065] The ammonia absorption capacity of the prepared sodium zirconium phosphate powder is 22.1 mmol / g, and after 15 cycles of use, the ammonia absorption capacity is 20.3 mmol / g.
[0066] Example 2
[0067] The steps for preparing sodium zirconium phosphate powder are as follows:
[0068] 100 kg of zirconium oxychloride raw material and 400 kg of solid zirconium carbonate were added to 500 kg of pure water (endotoxin value < 0.05 EU / mL, conductivity < 1 μs / cm) to prepare a zirconium-containing slurry [concentration of zirconium element (ZrO2 wt%) was 19.6%].
[0069] 700 kg of zirconium-containing slurry (70% of the total amount) was added to the reactor, and then 3870 kg of phosphate mixed solution [366.5 kg of 85% phosphoric acid, 261 kg of sodium phosphate, 226 kg of sodium monohydrogen phosphate, and 192 kg of sodium dihydrogen phosphate] (70% of the total amount) was slowly added to the reactor, the temperature was maintained at 110 ° C, the stirring line speed was maintained at 3.0 m / s during the reaction, and zirconium phosphate slurry was gradually formed, and maintained for more than 1 hour to obtain the initial H + Type zirconium phosphate.
[0070] 300 kg of zirconium-containing slurry (30% of the total amount) was slowly added to the above zirconium phosphate slurry. The temperature was maintained at 110° C. and the stirring linear velocity was maintained at 3.0 m / s during the reaction.
[0071] 1660 kg of phosphate mixed solution [157 kg of 85% phosphoric acid, 112 kg of sodium phosphate, 97 kg of sodium monohydrogen phosphate, and 82 kg of sodium dihydrogen phosphate] (30% of the total amount) was slowly added to the above zirconium phosphate slurry. The reaction temperature was maintained at 110°C. The stirring line speed was maintained at 3.0 m / s during the reaction. During this process, the molar ratio of zirconium and phosphorus in the slurry reached 1:5, and the concentration of zirconium reached 3% (in terms of ZrO2 wt%). The reaction was continued for 2 hours to achieve molecular rearrangement and obtain secondary H + Type zirconium phosphate.
[0072] The obtained H + The zirconium phosphate slurry is dehydrated and washed with pure water, with the amount of washing water being 30 times the weight of the zirconium phosphate solid to remove most of the free phosphorus and impurity elements.
[0073] The dehydrated H + The type zirconium phosphate was placed in pure water again to re-prepare into zirconium phosphate slurry [the zirconium element concentration (as ZrO2wt%) was 3%].
[0074] 123.7 kg of sodium hydroxide was added as a sodium salt donor for the sodium addition reaction. + The molar ratio of zirconium ions in the zirconium phosphate slurry is 2:1, and 6.5 kg of sodium sulfate is added as a structural stabilizer. The reaction temperature is maintained at 110°C, the stirring line speed is maintained at 3.0 m / s, and the reaction is carried out for 24 hours to perform sodium addition reaction and structural stabilization reaction, wherein the concentration of the structural stabilizer in the slurry is 0.1%, and the molar ratio of the structural stabilizer to the zirconium ions in the slurry is 0.03:1, and Na + Type zirconium phosphate, that is, sodium zirconium phosphate slurry.
[0075] The pH of the sodium zirconium phosphate slurry was adjusted to 10 with sodium hydroxide.
[0076] The obtained sodium zirconium phosphate slurry is dehydrated and washed with pure water, with the washing water amount being 80 times the weight of the sodium zirconium phosphate solid weight, to remove residual free phosphorus and impurity elements.
[0077] The sodium zirconium phosphate solid is dried at 30°C to a LOD value of 20%, so that the material has fluidity and the structural stability of the sodium zirconium phosphate is enhanced.
[0078] The dried sodium zirconium phosphate solid is screened to remove the lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder.
[0079] The prepared sodium zirconium phosphate powder has an ammonia absorption capacity of 25.2 mmol / g, and after 15 cycles of use, its ammonia absorption capacity is 23.2 mmol / g.
[0080] Example 3
[0081] The steps for preparing sodium zirconium phosphate powder are as follows:
[0082] 500 kg of zirconium nitrate raw material was dissolved in 500 kg of pure water (endotoxin value < 0.25 EU / mL, conductivity < 5 μs / cm) to prepare zirconium nitrate slurry [concentration of zirconium element (ZrO2 wt%) was 20%].
[0083] 450 kg of zirconium nitrate slurry (45% of the total amount) and 252 kg of phosphoric acid (45% of the total amount) were slowly added to the reactor at the same time. The reaction temperature was maintained at 70 ° C. During the reaction, the stirring line speed was maintained at 2.6 m / s to gradually form zirconium phosphate slurry. The slurry was maintained for 3 hours to obtain the initial H + Type zirconium phosphate.
[0084] 550 kg of zirconium nitrate slurry (55% of the total amount) was slowly added to the above zirconium phosphate slurry. The reaction temperature was maintained at 70° C. and the stirring linear velocity was maintained at 2.6 m / s during the reaction.
[0085] 308 kg of phosphoric acid (55% of the total amount) was slowly added to the above zirconium phosphate slurry. The reaction temperature was maintained at 70 ° C. The stirring speed was maintained at 2.6 m / s during the reaction. During this process, the molar ratio of zirconium and phosphorus in the slurry reached 1:3, and the concentration of zirconium reached 10% (in terms of ZrO2 wt%). The reaction was continued for 3 hours to achieve molecular rearrangement and obtain secondary H + Type zirconium phosphate.
[0086] The obtained H + The zirconium phosphate slurry is dehydrated and washed with pure water, with the amount of washing water being 20 times the weight of the zirconium phosphate solid to remove most of the free phosphorus and impurity elements.
[0087] The dehydrated H + The type zirconium phosphate was placed in pure water again to re-prepare into zirconium phosphate slurry [the zirconium element concentration (as ZrO2wt%) was 10%].
[0088] 130 kg of sodium hydroxide was added as the sodium salt donor for the sodium addition reaction. + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.8:1, and 100 kg of sodium nitrate is added as a structural stabilizer. The temperature is maintained at 110 ° C. The stirring line speed is maintained at 2.6 m / s, and sodium addition reaction and structural stabilization reaction are carried out, wherein the concentration of the structural stabilizer in the slurry is 5%, and the molar ratio of the structural stabilizer to the zirconium ions in the slurry is 0.72:1. The reaction is carried out for 12 hours to obtain Na + Type zirconium phosphate, i.e. sodium zirconium phosphate slurry
[0089] The pH of the slurry was adjusted to 5.7 with sodium hydroxide and phosphoric acid.
[0090] The obtained sodium zirconium phosphate slurry is dehydrated and washed with pure water, with the washing water amount being 40 times the weight of the sodium zirconium phosphate solid weight, to remove residual free phosphorus and impurity elements.
[0091] The sodium zirconium phosphate solid is dried at 100° C. to a LOD value of 14%, so that the material has fluidity and the structural stability of the sodium zirconium phosphate is enhanced.
[0092] The dried sodium zirconium phosphate solid is screened to remove the lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder.
[0093] The ammonia absorption capacity of the sodium zirconium phosphate powder is 28.7 mmol / g, and after 15 cycles of use, the ammonia absorption capacity is 26.7 mmol / g.
[0094] Example 4
[0095] The steps for preparing sodium zirconium phosphate powder are as follows:
[0096] 400 kg of zirconium sulfate and 100 kg of zirconium acetylacetonate raw materials were dissolved in 500 kg of pure water (endotoxin value < 0.05 EU / mL, conductivity < 1 μs / cm) to prepare a zirconium-containing slurry [zirconium element (ZrO2 wt%) concentration of 15%].
[0097] 300 kg of zirconium-containing slurry (30% of the total amount) and 300 kg of phosphate mixed solution [63 kg of 85% phosphoric acid, 146 kg of sodium dihydrogen phosphate] (30% of the total amount) were slowly added to the reactor at the same time. The temperature was maintained at 100 ° C. During the reaction, the stirring speed was maintained at 2.8 m / s to gradually form zirconium phosphate slurry. The slurry was maintained for 2 hours to obtain the initial H + Type zirconium phosphate.
[0098] 700 kg of zirconium-containing slurry (70% of the total amount) was slowly added to the above zirconium phosphate slurry. The temperature was maintained at 100° C. and the stirring linear speed was maintained at 2.8 m / s during the reaction.
[0099] 700 kg of phosphate solution [147 kg of 85% phosphoric acid, 341 kg of sodium dihydrogen phosphate] (70% of the total amount) was slowly added to the above zirconium phosphate slurry. The temperature was maintained at 100 ° C. The stirring speed was maintained at 2.8 m / s during the reaction. During this process, the molar ratio of zirconium and phosphorus in the slurry reached 1:2.5, and the concentration of zirconium reached 7.5% (in terms of ZrO2 wt%). The reaction was continued for 1.5 hours to achieve molecular rearrangement and obtain secondary H + Type zirconium phosphate.
[0100] The obtained H+ The zirconium phosphate slurry is dehydrated and washed with pure water, with the amount of washing water being 30 times the weight of the zirconium phosphate solid to remove most of the free phosphorus and impurity elements.
[0101] The dehydrated H + The type zirconium phosphate was placed in pure water again to re-prepare into zirconium phosphate slurry [the zirconium element concentration (as ZrO2wt%) was 7.5%].
[0102] 97 kg of sodium hydroxide was added as a sodium salt donor for the sodium addition reaction. + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.5:1, and 20kg of sodium phosphate and 20kg of sodium metaphosphate are added as structural stabilizers. The reaction temperature is maintained at 50°C, the stirring line speed is maintained at 2.8m / s, and the reaction is carried out for 24h to perform sodium addition reaction and structural stabilization reaction, wherein the concentration of the structural stabilizer in the slurry is 2%, and the molar ratio of the structural stabilizer to the zirconium ions in the slurry is 0.26:1, to obtain Na + Type zirconium phosphate, that is, sodium zirconium phosphate slurry.
[0103] The pH of the sodium zirconium phosphate slurry was adjusted to 4.0 with sodium hydroxide and hydrochloric acid.
[0104] The obtained sodium zirconium phosphate slurry is dehydrated and washed with pure water, with the washing water amount being 80 times the weight of the sodium zirconium phosphate solid weight, to remove residual free phosphorus and impurity elements.
[0105] The sodium zirconium phosphate solid is dried at 50°C to a LOD value of 12%, so that the material has fluidity and the structural stability of the sodium zirconium phosphate is enhanced.
[0106] The dried sodium zirconium phosphate solid is screened to remove the lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder.
[0107] The ammonia absorption capacity of the sodium zirconium phosphate powder is 31.1 mmol / g, and after 15 cycles of use, the ammonia absorption capacity is 29.5 mmol / g.
[0108] 1. Sodium zirconium phosphate powder form
[0109] This experiment provides SEM images of zirconium phosphate without molecular structure rearrangement, layered α-zirconium phosphate, and sodium zirconium phosphate powder prepared in Example 1 of the present invention. Among them:
[0110] The preparation method of zirconium phosphate without molecular structure rearrangement comprises the following steps:
[0111] 1100g of zirconium oxychloride slurry [concentration (ZrO2 wt%) 18%] is added to 1250g of phosphoric acid solution [concentration (PO4 wt%) 10%], react at room temperature for more than 1h, add ammonia water (concentration 20%) to adjust the pH of the slurry to 7, wash with 30 times of water, dehydrate and dry to obtain a zirconium phosphate product without molecular structure rearrangement. The molar ratio of zirconium element and phosphorus element can be widely adjusted according to the proportioning requirements, but the solution with phosphate radicals will quickly generate irregular zirconium phosphate products when encountering zirconium salt solution, which greatly limits its application in applications with morphology requirements. Therefore, the morphology of such products is not standardized or limitedly depends on the morphology of zirconium raw materials.
[0112] The layered alpha zirconium phosphate is prepared by the method in Chinese Patent No. 201110134080.6 (hydrothermal method) and the method in Chinese Patent No. 201110134080.6 (high temperature thermal cycle).
[0113] The SEM image of zirconium phosphate without molecular structure rearrangement is as follows: Figure 1 The SEM image of layered α-zirconium phosphate prepared by hydrothermal method is shown in Figure 2 The SEM image of layered α-zirconium phosphate prepared by high temperature thermal cycling is shown in Figure 3 As shown, the SEM image of the sodium zirconium phosphate powder prepared in Example 1 of the present invention is as follows Figure 4 shown.
[0114] From the above SEM images, it can be seen that due to the strong binding ability between phosphate and zirconium ions in the solution, insoluble zirconium phosphate precipitation can be formed instantly. Therefore, the molecular structure of the instantly formed zirconium phosphate is not rearranged, such as Figure 1 As shown, its structure is disordered. However, the sodium zirconium phosphate prepared by the present invention has a regular shape and is spherical. This shape breaks through the inherent shape of sodium zirconium phosphate in the prior art, achieves breakthroughs in the orderly growth of sodium zirconium phosphate particles, molecular structure rearrangement, and molecular structure stability, and forms a new sodium zirconium phosphate powder, avoiding the influence of small particle size or disordered particles on the performance of zirconium phosphate.
[0115] 2. Sodium zirconium phosphate particle size range
[0116] The particle size of the sodium zirconium phosphate prepared in Example 1 was tested using a Mastersizer 2000 particle size analyzer.
[0117] The test results are as follows Figure 5 As shown:
[0118] The particle size range is: D10>40μm, 60μm<D50<80μm, D90<100μm, and the D90 value is less than or equal to twice its D10 value.
[0119] 3. Characterization of Sodium Zirconium Phosphate Powder
[0120] The physical properties of sodium zirconium phosphate powder were characterized as follows:
[0121] The bulk density of sodium zirconium phosphate powder was tested by Hall flow meter; the tap density of sodium zirconium phosphate powder was tested by tap density meter; the Hausner ratio of powder = tap density / bulk density;
[0122] Weigh a certain amount of sodium zirconium phosphate powder and fill it into an ion exchange column, inject the prepared ammonium chloride solution into the ion exchange column at a certain flow rate, and regularly sample and test the ammonium ion concentration in the effluent until the sodium zirconium phosphate powder no longer absorbs ammonium ions, weigh the total weight of the effluent and calculate the ammonia absorption capacity of the sodium zirconium phosphate powder per unit weight;
[0123] The phosphate concentration in the effluent was tested by using an enzyme marker, and the free phosphorus per unit weight of the sodium zirconium phosphate powder was calculated;
[0124] The prepared sodium carbonate and sodium bicarbonate solutions were injected into the above-mentioned sodium zirconium phosphate ion exchange column which has been saturated with adsorption at a certain flow rate until the pH value of the effluent entered the predetermined range, which was considered as a successful regeneration. The prepared ammonium chloride solution was injected again to test the ammonia absorption capacity after regeneration, and the process was repeated 15 times to obtain the regeneration capacity;
[0125] Sodium zirconium phosphate powder is added into physiological saline to form a sodium zirconium phosphate slurry of a specific concentration, and the pH value of the slurry is tested at room temperature, which is defined as the pH value of the sodium zirconium phosphate powder;
[0126] The particle size of sodium zirconium phosphate powder was tested using MasterSize-2000MU particle size analyzer, and the D10, D50, and D90 values of the powder particle size were recorded;
[0127] The weight loss of sodium zirconium phosphate powder under the conditions of specific mass, oven temperature and time is defined as the LOD value of sodium zirconium phosphate powder;
[0128] The mouse fibroblast culture method was used to determine the survival rate of mouse cells under different concentrations of sodium zirconium phosphate leaching solution, which was used as the basis for the cytotoxicity of sodium zirconium phosphate powder.
[0129] Sodium zirconium phosphate powder is added to a sterile diluent to prepare a gradient concentration homogenate, and the total aerobic microorganisms and total mold and yeast are counted after culturing in a sterile culture dish for 5 days;
[0130] A certain amount of sodium zirconium phosphate powder was added into a certain amount of sterile water, and the endotoxin and element precipitation values in the supernatant were tested after shaking at 37°C.
[0131] The above test results are shown in Table 1:
[0132] Table 1 Characterization of sodium zirconium phosphate powder
[0133]
[0134] As shown in Table 1, the particle size range (PSD) of the sodium zirconium phosphate powder prepared by the present invention is: D10>40μm, 60μm<D50<80μm, D90<100μm, and the D90 value is less than or equal to 2 times of its D10 value; its cation (NH 4+ ) exchange capacity ≥ 22mg / g, up to 30mg / g; after sufficient ion exchange, the powder can be regenerated under appropriate conditions, and the cation (NH 4+ ) The exchange capacity is not less than 90% of the original powder, and the regeneration times are not less than 15 times; its pH range can be between 2 and 10; its water content (LOD) is between 8 and 20%; its bulk density range is between 1.15 and 1.35 g / cm 3 , the tap density range is 1.40~1.55g / cm 3 Its Hausner ratio (ratio of tap density to bulk density) is less than 1.30 and can be as low as 1.20; its free phosphorus value is less than 2300 mg / kg and can be as low as 1500 mg / kg; its endotoxin value is less than 0.2 EU / g and can be as low as 0.1 EU / g; its total aerobic microbial count (TAMC value) and total mold and yeast count (TYMC value) are both less than 70 CFU / g and can be as low as 10 CFU / g; its cytotoxicity test (survival rate under 100% extract) is greater than 70%; its Zr element precipitation value in 37°C pure water is less than 10 μg / g.
[0135] The bulk density and tap density of the material are crucial to the filling operation of sodium zirconium phosphate powder. The bulk density of the material decreases as the particle size decreases, and the state of the material gradually becomes fluffy, while the tap density is less affected by the reduction in particle size. Therefore, the reduction in particle size will cause the Hausner ratio (ratio of tap density to bulk density) of the material to increase. When filling powder into the adsorption tank, materials with a large Hausner ratio will form a gap between the material and the adsorption tank due to gravity and vibration, thereby affecting the dialysis reaction. The bulk density and tap density of sodium zirconium phosphate are not only related to the particle size and distribution of the powder, but also to the moisture content of the material. The higher the moisture content, the smaller the bulk density and tap density.
[0136] The particle size range (PSD) of the sodium zirconium phosphate powder prepared by the present invention is: D10>40μm, 60μm<D50<80μm, D90<100μm, and the D90 value is less than or equal to twice its D10 value; the moisture content (LOD) is controlled in the range of 8%-20%. Under the above conditions, the bulk density of sodium zirconium phosphate should be in the range of 1.15-1.35g / cm 3 ; The tap density should be in the range of 1.40~1.55g / cm 3 The Hausner ratio of the powder should be less than 1.3, and more preferably less than 1.2, so that the material will not form large gaps in the adsorption tank due to vibration or gravity.
[0137] Another key feature of sodium zirconium phosphate powder used in hemodialysis is the low phosphate precipitation. Although the precipitated phosphate can be adsorbed by zirconium hydroxide or zirconium carbonate (or sodium zirconium carbonate), excessive phosphate precipitation will inevitably lead to an increase in the dosage of zirconium hydroxide (or sodium zirconium carbonate) and the complication of the hemodialysis procedure. The main source of phosphorus precipitation in sodium zirconium phosphate is the initial H + The control of free phosphate is not only directly related to the molar ratio of zirconium element and phosphate, the degree of water washing, the size and particle size distribution of particles, but also directly related to the structural stability of sodium zirconium phosphate. It is generally believed that the smaller the molar ratio of zirconium element and phosphate, the higher the phosphorus precipitation; the smaller the sodium zirconium phosphate particles, the higher the phosphorus precipitation; the wider the particle size distribution range of sodium zirconium phosphate, the higher the phosphorus precipitation; the lower the water volume of water washing, the higher the phosphorus precipitation; the less the amount of structural stabilizer, the higher the phosphorus precipitation; the worse the structural stability of zirconium phosphate, the higher the phosphorus precipitation. Therefore, the suitable sodium zirconium phosphate powder should strictly control the molar ratio of zirconium element and phosphate, the degree of water washing of materials, the size and particle size distribution of particles, and the amount of structural stabilizer, reaction time and temperature, drying conditions, etc. during the sodium addition reaction should also be strictly controlled.
[0138] The main biological indicators of sodium zirconium phosphate powder are endotoxin, microorganisms, and cytotoxicity. Endotoxin is caused by lipopolysaccharide in the cell wall of Gram-negative bacteria. Lipopolysaccharide is toxic to patients undergoing hemodialysis and can cause symptoms such as fever, microcirculatory disorders, endotoxin shock, and disseminated intravascular coagulation. Therefore, the endotoxin content in sodium zirconium phosphate powder should be strictly controlled to less than 0.2Eu / g. Endotoxin in sodium zirconium phosphate can be removed by long-term high temperature, but long-term high temperature may cause the cation exchange capacity of sodium zirconium phosphate powder to decrease. The main raw materials for the production of sodium zirconium phosphate do not contain endotoxin, and its main source is Gram-negative bacteria in production water. Therefore, strict control of Gram-negative bacteria in production water is an important means to prevent endotoxin from exceeding the standard. Ultrafiltration, reverse osmosis, ion exchange, etc. can usually be used to control the endotoxin value in production water to ≤0.25Eu / mL, which can effectively prevent endotoxin from exceeding the standard in sodium zirconium phosphate powder. The total oxygen microbial count (TAMC) in sodium zirconium phosphate powder should be less than 70 CFU / g, and the total yeast and mold count (TYMC) should also be less than 70 CFU / g. The microorganisms in sodium zirconium phosphate also come from production water, production equipment and external environment. In addition to strictly controlling the microorganisms in production water, the contact between non-clean air and materials should be avoided as much as possible during the production process. Usually, it is produced in a 10,000-level (or above) clean workshop or the air in contact with the material is filtered with a 0.5-5μm filter, which can fully isolate external microorganisms and meet the requirements of microbial indicators. There are many factors that affect the cytotoxicity of materials. In addition to factors such as pH and microorganisms of the material, it is also related to the free phosphoric acid of sodium zirconium phosphate, the chemicals used in the preparation process, and the amount of element precipitation. Therefore, in the preparation process of sodium zirconium phosphate, the pH should be strictly controlled within a certain range. At the same time, the introduction of toxic and harmful substances should be avoided during the production process. At the same time, the structural stability of sodium zirconium phosphate should be ensured to avoid excessive element precipitation or phosphate precipitation.
[0139] In the preparation process of sodium zirconium phosphate, the control of moisture content (LOD) is also crucial. In addition to directly affecting the cation exchange capacity of sodium zirconium phosphate powder, this process will also affect key indicators such as material density, regeneration capacity, and element precipitation. The control of moisture content is mainly achieved through drying temperature and time. When LOD>20%, the sodium zirconium phosphate material cannot show a flow state due to its high moisture content and cannot be filled. However, when LOD<8%, the active H in the sodium zirconium phosphate molecule + It will be destroyed as the water evaporates, thus seriously reducing the cation exchange capacity of the powder. The drying temperature also has a direct impact on the performance of the powder. Too high a drying temperature will directly destroy the active H in the sodium zirconium phosphate molecule. +, which seriously affects the cation exchange capacity of the powder. Appropriate drying conditions and LOD control can also make the molecular structure of sodium zirconium phosphate more stable, effectively reduce the precipitation of phosphate and elements (mainly zirconium), and help the cyclic regeneration of the cation exchange capacity of sodium zirconium phosphate. The structural stability of sodium zirconium phosphate is lower than that of zirconium phosphate. When undergoing ion exchange reaction with dialysate, zirconium ions will inevitably precipitate from the sodium zirconium phosphate molecules. The amount of precipitation is closely related to the pH control during the preparation process, the stability of the molecular structure, and the composition of the dialysate.
[0140] As can be seen from the above content, the sodium zirconium phosphate powder prepared by the present invention is spherical and has a narrow particle size distribution range. The advantage of this structure is that the powder has excellent fluidity, so that the powder can be evenly filled into various positions of the adsorbent tank during the filling process, and when the dialysate passes through, the dialysate can flow evenly through the gaps between the sodium zirconium phosphate powders, and no local blockage or excessive pressure will be generated due to uneven distribution of particles.
[0141] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing spherical sodium zirconium phosphate powder, characterized in that: The steps include: (1) Preparation of zirconium-containing slurry dissolving a zirconium raw material in water to prepare a zirconium-containing slurry; (2) Preparation of initial H + Zirconium phosphate The zirconium-containing slurry and phosphate raw materials are added to the reactor and reacted at 25-110°C and a stirring speed of >2.5 m / s to obtain the initial H + Type zirconium phosphate; (3) Preparation of secondary H + Zirconium phosphate At 25-110°C and stirring speed > 2.5 m / s, add the zirconium slurry to the primary H + The phosphate raw material is then added to the zirconium phosphate slurry to react and obtain the secondary H + Type zirconium phosphate; (4) Slurry dehydration and reconditioning The secondary H + The zirconium phosphate slurry is dehydrated and washed to remove free phosphorus and impurity elements, and then the dehydrated H + The zirconium phosphate was placed in water and re-prepared into H + Type zirconium phosphate slurry; (5) Preparation of sodium zirconium phosphate slurry In H + Sodium salt and structural stabilizer are added to the zirconium phosphate slurry, and reacted at 25-110°C and stirring line speed>2.5m / s to perform sodium addition reaction and structural stabilization reaction to obtain Na + Type zirconium phosphate, i.e. sodium zirconium phosphate slurry; (6) Obtaining sodium zirconium phosphate powder Adjusting the pH of the sodium zirconium phosphate slurry to 2-10; Dehydrating and washing to remove residual free phosphorus and impurity elements; then drying the sodium zirconium phosphate solid at 30-270°C to a moisture content of 8-20%, and then sieving the sodium zirconium phosphate solid to remove lumps and fine powder generated by agglomeration during the drying process to obtain sodium zirconium phosphate powder; In the step (1), the zirconium raw material is selected from one or more of zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium carbonate, and zirconium acetylacetonate; in the step (2), the phosphate raw material is selected from one or more of phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, and sodium dihydrogen phosphate; in the step (5), the sodium salt is selected from one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate; in the step (5), the structural stabilizer is selected from one or more of sodium chloride, sodium sulfate, sodium nitrate, sodium metaphosphate, and sodium phosphate; In the step (1), the concentration of zirconium in the zirconium-containing slurry is selected from 3 to 20%; in the step (2), the amount of the zirconium-containing slurry is selected from 10 to 70% of the total amount of the zirconium-containing slurry, and the amount of the phosphate raw material is selected from 10 to 70% of the total amount of the phosphate raw material; in the step (3), the amount of the zirconium-containing slurry is selected from 30 to 90% of the total amount of the zirconium-containing slurry, and the amount of the phosphate raw material is selected from 30 to 90% of the total amount of the phosphate raw material; in the step (4), the re-prepared H + The concentration of zirconium element in the zirconium phosphate slurry is selected from 3 to 20%; In the step (5), the structural stabilizer and H + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.03 to 1:1; the sodium salt and H + The molar ratio of zirconium ions in the zirconium phosphate slurry is selected from 0.1 to 2:
1.
2. The preparation method according to claim 1, characterized in that: In the step (6), one or more of hydrochloric acid, phosphoric acid and sodium hydroxide are used to adjust the pH.
3. The preparation method according to claim 1, characterized in that: In the steps (2), (3) and (5), the reaction time is at least 1 hour.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the zirconium element in the total amount of the zirconium-containing slurry used to the phosphate in the total amount of the phosphate raw material used is selected from 1:1.5-5.
5. The preparation method according to claim 1, characterized in that: The washing is to use 10 to 80 times the weight of the sodium zirconium phosphate solid to wash the dehydrated sodium zirconium phosphate solid to remove residual free phosphorus and impurity elements.
6. Spherical sodium zirconium phosphate powder prepared by the method according to any one of claims 1 to 5.
7. Use of the spherical sodium zirconium phosphate powder according to claim 6 in preparing hemodialysis materials.
Citation Information
Patent Citations
Sphere analogous alpha-zirconium phosphate and preparing method thereof
CN100532253C
Method for preparing sodium hydrogen zirconium phosphate powder
CN102180455A
Rod-shaped zirconium phosphate and preparation method thereof
CN102992293A
Cubic zirconium phosphate and preparation method thereof
CN103101896A
Preparation method of sodium zirconium phosphate powder with high cation exchange capacity
CN111498824A